High-performance Thin-layer Chromatography Fingerprinting Analysis of Punarnavadi Kwatha - Vijayan, Resmi; Ansary, P Y; Oommen, Sara Moncy; Shincymol, V V (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Punarnavadi kwatha is one among the commonly used medicine in Ayurvedic practice, mentioned in Chakradatta in sopha chikitsa. Main indications of Punarnavadi kwatha are Sarvanga sopha (generalised oedema), Udara (ascites), Kasa (cough), Soolam (colicky pain), and Swasa (dyspnoea) associated with Pandu (anaemia). For the purpose of quality assurance and uniformity, scientific verification of Ayurvedic medications is important. Usage of modern analytical techniques helps in the proper authentication of medicines. In the present study, high performance thin-layer chromatography (HPTLC) fingerprinting of Punarnavadi kwatha aimed to assess the different phytoconstituents. Materials and Methods: Methanolic extract of Punarnavadi kwatha was subjected to HPTLC fingerprinting using the solvent system toluene:ethyl acetate:formic acid (6:3:0.5). Toluene is a least polar solvent, ethyl acetate is mid polar solvent and formic acid is highly polar so in this solvent system, maximum separation of compounds took place. Results and Discussion: The number of peaks obtained at visualization 254 nm was 8 and total area of compounds in is 30309.5. Visualization at 366 nm, number of peaks was 12 and total area is 42473.2. Conclusion: Thus, the study revealed that HPTLC fingerprinting of formulations can be used in the quality control of ayurvedic medicaments. The maximum separation of compounds occurred at this solvent system.